Effect of live yeast supplementation on performance parameters of Jersey cows grazing ryegrass/kikuyu pasture - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2011.